Sustainable conversion of alkaline nitrate to ammonia at activities greater than 2 A cm−2 - Liao, Wanru; Wang, Jun; Ni, Ganghai; Liu, Kang; Liu, Changxu; Chen, Shanyong; Wang, Qiyou; Chen, Yingkang; Luo, Tao; Wang, Xiqing; Wang, Yanqiu; Li, Wenzhang; et al. (Nature communications, 2024)
Nitrate (NO 3 ‒ ) pollution poses significant threats to water quality and global nitrogen cycles. Alkaline electrocatalytic NO 3 ‒ reduction reaction (NO 3 RR) emerges as an attractive route for enabling NO 3 ‒ removal and sustainable ammonia (NH 3 ) synthesis. However, it suffers from insufficient proton (H + ) supply in high pH conditions, restricting NO 3 ‒ -to-NH 3 activity. Herein, we propose a halogen-mediated H + feeding strategy to enhance the alkaline NO 3 RR performance. Our platform achieves near-100% NH 3 Faradaic efficiency (pH = 14) with a current density of 2 A cm –2 and enables an over 99% NO 3 – -to-NH 3 conversion efficiency. We also convert NO 3 ‒ to high-purity NH 4 Cl with near-unity efficiency, suggesting a practical approach to valorizing pollutants into valuable ammonia products. Theoretical simulations and in situ experiments reveal that Cl-coordination endows a shifted d -band center of Pd atoms to construct local H + -abundant environments, through arousing dangling O-H water dissociation and fast *H desorption, for *NO intermediate hydrogenation and finally effective NO 3 ‒ -to-NH 3 conversion. Alkaline nitrate electroreduction to ammonia is restricted by insufficient H + supply. Here, the authors propose a halogen-mediated H + feeding strategy, by triggering dangling O-H water dissociation and fast *H desorption for *NO intermediate hydrogenation, to enhance the formation of ammonia.